Protocol for the Exercise, Cancer and Cognition – The ECCO-Study: A Randomized Controlled Trial of Simultaneous Exercise During Neo-/Adjuvant Chemotherapy in Breast Cancer Patients and Its Effects on Neurocognition - Kiesl, David; Kuzdas-Sallaberger, Marina; Fuchs, David; Brunner, Silvana; Kommenda, Romana; Tischler, Clemens; Hornich, Herwig; Akbari, Kaveh; Kellermair, Jörg; Blessberger, Hermann; Ocenasek, Helmuth; Hofmann, Peter; et al. (Frontiers in Neurology, 2022)
Introduction Epidemiological studies show that increased physical activity is linked to a lower risk of breast cancer and mortality. As a result, physical activity can significantly improve patients' quality of life (QOL) both during and after therapy. Many breast cancer patients demonstrate a decrease in cognitive capacity, referred to as the symptom-complex cancer related cognitive impairment (CRCI). Most frequently reported impairments are mild to moderate deficits in processing speed, attention, memory, and executive functions. Cognitive symptoms persist for months or even years, following medical treatment in roughly 35% of afflicted people, impairing everyday functioning, limiting the ability to return to work, and lowering the overall QOL. Recent studies point toward a key role of inflammatory pathways in the CRCI genesis. Attention to physical activity as a potential supportive care option is therefore increasing. However, evidence for the positive effects of exercise on preventing CRCI is still lacking. Patients and Methods Against this background, the prospective, two-arm, 1:1 randomized, controlled trial investigates the influence of first line chemotherapy accompanied by exercise training on preventing CRCI in 126 patients with breast cancer at the local University Hospital. The study will evaluate biomarkers and secondary assessments suspected to be involved in the pathogenesis of CRCI in addition to objective (primary outcome) and subjective cognitive function. CRCI is believed to be connected to either functional and/or morphological hippocampal damage due to chemotherapy. Thus, cerebral magnetic resonance imaging (MRI) and hippocampal volume measurements are performed. Furthermore, a specific neuropsychological test battery for breast cancer patients has been developed to detect early signs of cognitive impairments in patients and to be integrated into practice. Discussion This study will explore how a long-term supervised exercise intervention program might prevent CRCI, enables optimization of supportive care and objectifies limits of psychological and physical resilience in breast cancer patients during and after chemotherapy treatment. Trial Registration ClinicalTrials.gov: Identifier: NCT04789187. Registered on 09 March 2021.